Pendidikan Politik Sebagai Upaya untuk Mengantisipasi Maraknya Politik Identitas pada Pemilihan Umum - Nuryadi, Muhammad Hendri; Widiatmaka, Pipit (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to analyze strategies for anticipating identity politics in general elections, the role and objectives of political education, as well as the implications of political education for social harmony. This study uses a qualitative approach with a library research type of research. The results of the study show that the strategy that can be used to anticipate identity politics in general elections is through political education. Political education has a role in forming a politically literate society. The aim of political education is to provide knowledge about politics to the public so that they are able to participate actively in the political system. Political education has implications for social harmony because it is carried out by upholding human values without discrimination